Analisis Kesehatan Gigi di Lingkungan Universitas Kadiri (Unik) dengan Intervensi Scalling Gratis dan Penyuluhan Kesehatan Gigi Tahun 2025 - Widiastomo, Joko (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Oral and dental health is an important aspect of individual well-being that is often neglected by students and faculty in academic environments. This study aims to analyze the oral and dental health conditions at Kadiri University and evaluate the effectiveness of an intervention involving free scaling and dental health counseling. The research methodology used is a quantitative and qualitative approach, with data collection through clinical examinations, satisfaction surveys, and participant interviews. The results of the study show that before the intervention, the prevalence of dental caries was relatively high (approximately 76.7%). After the intervention, there was a 70% increase in knowledge and adherence to maintaining oral hygiene. Additionally, the majority of respondents (93.33%) expressed satisfaction with the program provided. Therefore, this intervention has proven effective in improving oral and dental health and raising awareness of the importance of regular care.